Interventions on informal healthcare providers to improve the delivery of healthcare services in low-and middle-income countries: a systematic review - Das, Saibal; Khare, Shweta; Eriksen, Jaran; Diwan, Vishal; Stålsby Lundborg, Cecilia; Skender, Kristina (Frontiers in Public Health, 2024)
Objective Informal healthcare providers (IHCPs) play a big role in health systems in low-and middle-income countries (LMICs) and are often the first point of contact for healthcare in rural and underserved areas where formal healthcare infrastructure is insufficient or absent. This study was performed to systematically review the literature on interventions targeting IHCPs in improving the delivery of healthcare services in LMICs. Methods PubMed, Embase, and Cochrane CENTRAL databases were searched for studies that assessed any type of intervention among IHCPs to improve the delivery of healthcare services in any LMIC. Outcomes included changes in knowledge, attitude, and reported practice of appropriate case diagnosis and management; improved referral services; effective contraceptive use; and medication appropriateness (PROSPERO ID: CRD42024521739). Results A total of 7,255 studies were screened and 38 were included. Most of the studies were conducted in Africa and Asia. The IHCPs who were trained included medicine sellers, community health workers/traditional healers, and traditional birth attendants. The main intervention used was educational programs in the form of training. The other interventions were health services, policy and guidelines, and community-based interventions. Most of the interventions were multi-faceted. The disease/service areas targeted were mainly maternal and child health, sexually transmitted diseases, common infectious diseases, medicine use/dispensing practices, and contraception. The outcomes that showed improvements were knowledge, attitude, and reported practice; diagnosis and case management; improved referral services; contraceptive uses; and medication appropriateness. Around one-fourth of the studies reported negative results. The certainty of evidence generated (GRADE criteria) was very low. Conclusion Some multifaceted interventions coupled with training showed improvements in the delivery of healthcare services by IHCPs. However, the improvements were inconsistent. Hence, it is unclear to identify any context-specific optimum intervention to improve the delivery of healthcare services by IHCPs.